IMPROVING THE ANALYSIS OF FINANCIAL STATEMENTS IN COMMERCIAL BANKS - Meliboev Adxamjon Kurvonalievich (Scholar Express Journals, 2023)
This article explores strategies for improving the analysis of financial statements in commercial banks. It employs a multi-faceted approach, encompassing key financial ratios, trend analysis, and advanced data analytics techniques.
Keywords: Financial statement analysis; commercial banks; key financial ratios